Sensing behavior of atomically thin-layered MoS2 transistors - Late, Dattatray J.; Huang, Yi-Kai; Liu, Bin; Acharya, Jagaran; Shirodkar, Sharmila N.; Luo, Jiajun; Yan, Aiming; Charles, Daniel; Waghmare, Umesh V.; Dravid, Vinayak P.; Rao, C. N. R. (ACS Nano, 2013)
Most of recent research on layered chalcogenides is understandably focused on single atomic layers. However, it is unclear if single-layer units are the most ideal structures for enhanced gas solid interactions. To probe this issue further, we have prepared large-area MoS2 sheets ranging from single to multiple layers on 300 nm SiO2/Si substrates using the micromechanical exfoliation method. The thickness and layering of the sheets were identified by optical microscope, invoking recently reported specific optical color contrast, and further confirmed by AFM and Raman spectroscopy. The MoS2 transistors with different thicknesses were assessed for gas-sensing performances with exposure to NO2, NH3, and humidity in different conditions such as gate bias and light Irradiation. The results show that, compared to the single-layer counterpart, transistors of few MoS2 layers exhibit excellent sensitivity, recovery, and ability to be manipulated by gate bias and green light. Further, our ab initio DFT calculations on single-layer and bilayer MoS2 show that the charge transfer is the reason for the decrease in resistance in the presence of applied field.

Thermal expansion, anharmonicity and temperature-dependent Raman spectra of single- and few-layer MoSe2 and WSe2 - Late, Dattatray J.; Shirodkar, Sharmila N.; Waghmare, Umesh V.; Dravid, Vinayak P.; Rao, C. N. R. (ChemPhysChem, 2014)
We report the temperature-dependent Raman spectra of single-and few-layer MoSe2 and WSe2 in the range 77-700 K. We observed linear variation in the peak positions and widths of the bands arising from contributions of anharmonicity and thermal expansion. After characterization using atomic force microscopy and high-resolution transmission electron microscopy, the temperature coefficients of the Raman modes were determined. Interestingly, the temperature coefficient of the A(2u)(2) mode is larger than that of the A(1g) mode, the latter being much smaller than the corresponding temperature coefficients of the same mode in single-layer MoS2 and of the G band of graphene. The temperature coefficients of the two modes in single-layer MoSe2 are larger than those of the same modes in single-layer WSe2. We have estimated thermal expansion coefficients and temperature dependence of the vibrational frequencies of MoS2 and MoSe2 within a quasi-harmonic approximation, with inputs from first-principles calculations based on density functional theory. We show that the contrasting temperature dependence of the Raman-active mode A(1g) in MoS2 and MoSe2 arises essentially from the difference in their strainphonon coupling.